Differences in iodine chemistry over the Antarctic continent - Mahajan, Anoop S.; Wagh, Shrutika; Fernandez, Rafael Pedro; Singh, Surendra; Bucci, Silvia; Saiz López, Alfonso (Polar Science)
High concentrations of iodine oxide (IO) have been reported over west Antarctica, with areas around the Weddell Sea showing a peak in spring. However, stations in east Antarctica show much lower values during summer, although observations over spring are still missing. Here, we present the first year-long observations of IO outside the Weddell Sea region using a multi-axis differential optical absorption spectrometer (MAX-DOAS) over the Bharati station (69.41 ◦ S, 76.19 ◦ E). Observationsshow that iodine chemistry is less active than over the Weddell Sea, even during springtime, with IO mixing ratios below 2 pptv throughout the sunlit period. A slight increase in IO is observed in spring, although it is a factor of 10 lower than the Weddell Sea region. We identify the variations in drivers in the different regions using sea ice concentrations, sea ice thickness and chlorophyll concentrations. We use a global model which uses a parameterization for iodine emissions based on a combination of these factors. The model reproduces the high concentrations over the Weddell Sea and the low concentrations over Bharati throughout the year, shedding light on the environmental factors, sources and chemistry of iodine in Antarctica. Even at small concentrations, iodine can enhance ozone loss caused by bromine chemistry over east Antarctica, although this impact is lower than in the west Antarctic. Fil: Mahajan, Anoop S. Ministry of Earth Sciences. Indian Institute of Tropical Meteorology. Centre for Climate Change Research; India Fil: Wagh, Shrutika. Savitribai Phule Pune University; India. Ministry of Earth Sciences. Indian Institute of Tropical Meteorology. Centre for Climate Change Research; India Fil: Fernandez, Rafael Pedro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Interdisciplinario de Ciencias Básicas. - Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina Fil: Singh, Surendra. Ministry of Earth ...